m7G-Associated subtypes, tumor microenvironment, and validation of prognostic signature in lung adenocarcinoma - Wang, Guangyao; Zhao, Mei; Li, Jiao; Li, Guosheng; Zheng, Fukui; Xu, Guanglan; Hong, Xiaohua (Frontiers in Genetics, 2022)
Background: 7-Methylguanosine (m7G) is an important post-transcriptional modification that regulates gene expression and is involved in tumorigenesis and development. Tumor microenvironment has been proved to be highly involved in tumor progression and prognosis. However, how m7G-associated genes affect the tumor microenvironment of patients with lung adenocarcinoma (LUAD) remains to be further clarified. Methods: The genetic alterations of m7G-associated genes and their associations with the prognosis and tumor microenvironment in LUAD patients were systemically analyzed. A m7G-Riskscore was established and analyzed for its performance in prognosis and association with patient response to immunotherapy. Expression of the model genes at the protein level was examined through ex vivo experiments. A nomogram was finally obtained based on the m7G-Riskscore and several significant clinical pathological features. Results: m7G-associated genes were obtained from 4 LUAD datasets from TCGA and GEO databases and their expression pattern was determined. Based on the m7G-associated genes, 3 LUAD clusters were defined. The differentially expressed genes from the 3 clusters were screened out and used to further divide the LUAD patients into two gene-Clusters. It was demonstrated that the alterations of m7G-associated genes were associated with the clinical pathological features, prognosis and tumor immune infiltration in LUAD patients. A m7G-Riskscore including CAND1, RRM2 and SLC2A1 was obtained with robust and accurate prognostic performance. WB and cell immunofluorescence also showed significant dysregulation of CAND1, RRM2 and SLC2A1 in LUAD. In addition, a nomogram was established to improve the clinical feasibility of the m7G-Riskscore. Correlation analysis revealed that patients with a lower m7G-Riskscore had higher immune and stromal scores, responded well to chemotherapeutics and multiple targeted drugs and survived longer. Patients with a higher m7G-Riskscore tended to suffer from a higher tumor mutation burden. Furthermore, the m7G-Riskscore also exhibited significant associations with immune cell infiltration and cancer stemness. Conclusion: This study systemically analyzed m7G-associated genes and identified their potential role in tumor microenvironment and prognosis in patients with LUAD. Findings of the current study may help better understand LUAD from the m7G perspective and also provide a new thought toward prognosis and treatment of LUAD.